3D Geothermal Modelling Using Gravity Survey on Dolok Marawa, Simalungun District, North Sumatera. (January 2016) - Rivandi, A; Destawan, R; Fajri, Z R; Hidayat, W
Abstract: In North Sumatera, gravity method is applied to identify the geothermal model. This method measured the earth gravitational field. This research has 160 measurement points covering 9 square kilometers. We obtained complete Bouguer anomaly values ranging 85 mGal - 130.68 mGal interpreted as a heat source of andesitic igneous rocks that are affected by the presence of Mount Bahtopu magma chamber. We interpreted the values between 40 mGal - 80 mGal as reservoir and caprock. The 3D gravity inverse modelling conducted using Gravblox, and identifying the following lithologies; Toba Pyroclastic Fall (Qjt) with density 1.92 g/cm 3, Toba Pyroclastic Flow (Qjt) with density 2.00 g/cm 3, Mount Bahtopu Andesite (Qlb) with density 2.4 g/cm 3, and 2.6 g/cm 3 which is interpreted as heat source in form of andesitic rock and Mount Bahtopu magma chamber. This heat source is estimated to be at a depth of 1.45 km to 3.78 km below the surface.